Clinical Outcomes Associated With Acute Mechanical Circulatory Support Utilization in Heart Failure Related Cardiogenic Shock. (May 2021) - Hernandez-Montfort, Jaime; Sinha, Shashank S.; Thayer, Katherine L.; Whitehead, Evan H.; Pahuja, Mohit; Garan, Arthur Reshad; Mahr, Claudius; Haywood, Jillian L.; Harwani, Neil M.; Schaeffer, August; Wencker, Detlef; Kanwar, Manreet; et al.
Abstract : Background: Cardiogenic shock occurring in the setting of advanced heart failure (HF-CS) is increasingly common. However, recent studies have focused almost exclusively on acute myocardial infarction-related CS. We sought to define clinical, hemodynamic, metabolic, and treatment parameters associated with clinical outcomes among patients with HF-CS, using data from the Cardiogenic Shock Working Group registry. Methods: Patients with HF-CS were identified from the multicenter Cardiogenic Shock Working Group registry and divided into 3 outcome categories assessed at hospital discharge: mortality, heart replacement therapy (HRT: durable ventricular assist device or orthotopic heart transplant), or native heart survival. Clinical characteristics, hemodynamic, laboratory parameters, drug therapies, acute mechanical circulatory support device (AMCS) utilization, and Society of Cardiovascular Angiography and Intervention stages were compared across the 3 outcome cohorts. Results: Of the 712 patients with HF-CS identified, 180 (25.3%) died during their index admission, 277 (38.9%) underwent HRT (durable ventricular assist device or orthotopic heart transplant), and 255 (35.8%) experienced native heart survival without HRT. Patients who died had the highest right atrial pressure and heart rate and the lowest mean arterial pressure of the 3 outcome groups ( P <0.01 for all). Biventricular and isolated left ventricular congestion were common among patients who died or underwent HRT, respectively. Lactate, blood urea nitrogen, serum creatinine, and aspartate aminotransferase were highest in patients with HF-CS experiencing in-hospital death. Intraaortic balloon pump was the most commonly used AMCS device in the overall cohort and among patients receiving HRT. Patients receiving >1 AMCS device had the highest in-hospital mortality rate irrespective of the number of vasoactive drugs used. Mortality increased with deteriorating Society of Cardiovascular Angiography and Intervention stages (stage B: 0%, stage C: 10.7%, stage D: 29.4%, stage E: 54.5%, 1-way ANOVA=<0.001). Conclusions: Patients with HF-CS experiencing in-hospital mortality had a high prevalence of biventricular congestion and markers of end-organ hypoperfusion. Substantial heterogeneity exists with use of AMCS in HF-CS with intraaortic balloon pump being the most common device used and high rates of in-hospital mortality after exposure to >1 AMCS device. Abstract : Supplemental Digital Content is available in the text.